Ethanolic Extract of Black Rice ‘Sembada Hitam’ Bran Did not Show Cytotoxic Effect on HeLa Cell (Cervical Cancer Cell Line) - Nuriliani, Ardaning; Conara, Flafiani Cios; Oktavya, Galuh; Hidayah, Lailly Tsania Nur; Purwestri, Yekti Asih (Bioma : Berkala Ilmiah Biologi, 2023)
Black rice (Oryza sativa L.) contains various phenolic compounds such as anthocyanins which act as antioxidants. Antioxidants inhibit cell proliferation and induced apoptosis of cancer cells as well as protect cells from damage that triggers cancer. 'Sembada Hitam' is a new cultivar of black rice in Indonesia that has not been studied for its anticancer potential. This study aimed to study the cytotoxic activity and apoptosis induction of the ethanolic extract of black rice (Oryza sativa L. 'Sembada Hitam') bran against HeLa cells. The method used was the cytotoxicity test with the MTT assay and the apoptosis test with the AO-PI double staining method. The test used various concentrations of black rice bran extract, DMSO as solvent control, and doxorubicin as a positive control for 24 and 48 hours. Data analysis was performed using one-way ANOVA (p = 0.05) followed by the Tukey HSD test. The results showed that ethanolic extract of black rice 'Sembada Hitam' bran has no cytotoxic activity against HeLa cells (p > 0.05). Moreover, extracts at the concentrations of 250 and 500 µg/mL only induced apoptosis of HeLa cells by 11.62 ± 0.50 and 11.49 ± 9.88% respectively. These results indicate that the ethanolic extract of black rice 'Sembada Hitam' bran has no potential to be developed as an agent for cervical cancer therapy.